The Post harvest Storage of Garlic in East Java - Komar, Nur; Rakhmadiono, S.; Kurnia, Lina (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
Garlic, as an important commodity for various Indonesia unique cooking, is very wide in using. The continue demand of garlic need balancing supply in stock of it fulfils supply target.Â The good garlic storage method is very important factor on inventory control of it continually. In fact planting time schedule of garlic in some regions such as Brebes, Kediri, Malang, Jember and Banyuwangi are unmanaged. It is became constraints to regulate planting schedule of some garlic production regions center impact to price fluctuation by time and by locations.Technically, garlic defines as a tuber crops with layers, which outers layer is easy to dry and to get peeled off. It is the reason, why garlic easy to shrink, about 25%, when storage time in tropical regions, while in sub tropical region, the shrinkage is 17%.Laboratory experiment with empirically approach of garlic, expected to get a result a good performance with indicators as follow: 1) storage temperature, 2) relative humidity, 3) water content of garlic tightened, 4) decreasing respiration rate, 5) penetrometer index, 6) targeted storage time of garlic. The expected result is to get the best storage conditions to increasing garlic potency.Keywords: post harvest storage, garlic